Fashioning femininity for war: material culture and gender performance in the WAC and WAVES during World War II - Willey, Amanda Mae (Kansas State University, 2015)
In 1942, the U.S. Army and Navy announced the creation of their respective women’s military services: the WAAC/WAC and the WAVES. Although American women had served alongside the military in past conflicts, the creation of women’s military corps caused uproar in American society. Placing women directly into the armed services called into question cultural expectations about “masculinity” and “femininity.” Thus, the women’s corps had to be justified to the public in accordance with American cultural assumptions regarding proper gender roles. “Fashioning Femininity for War: Material Culture and Gender Performance in the WAC and WAVES during World War II” focuses on the role of material culture in communicating a feminine image of the WAC and WAVES to the American public as well as the ways in which servicewomen engaged material culture to fashion and perform a feminine identity compatible with contemporary understandings of “femininity.” Material culture served as a mechanism to resolve public concerns regarding both the femininity and the function of women in the military. WAC and WAVES material culture linked their wearers with stereotyped characteristics specifically related to contemporary meanings of “femininity” celebrated by American society, while at the same time associating them with military organizations doing vital war work. Ultimately, the WAVES were more successful in their manipulations of material culture than the WAC, communicating both femininity and function in a way that was complementary to the established gender hierarchy. Therefore, the WAVES enjoyed a prestigious position in the mind of the American public. This dissertation also contributes to the ongoing historiographical debate regarding World War II as a turning point for women’s liberation, arguing that while the seeds of women’s liberation were sown in women’s wartime activities, those same wartime women were firmly convinced that their rightful place was in the private rather than the public sphere. The war created an opportunity to reevaluate gender roles but it would take some time before those reevaluations bore fruit.
Keywords: military history; gender performance; material culturewomen's history; History (0578)